Supply chain redesign for resilience – the perspective of the consequences of disruption - Wieteska, Grażyna (Przeprojektowanie łańcucha dostaw w celu zapewnienia odporności – perspektywa skutków zakłócenia, 2019)
The purpose of this paper is to draw attention to the issue of “redesign” in the supply chain resilience concept as a way of dealing with the consequences of disruption. The article presents this issue in light of SCRES literature and survey results. The literature analysis allowed to identify key terminology (design, reconfiguration and redesign terms) and assign them to the specific phase of the disturbance. Additionally, the SCRES closed loop including five SCRES abilities is proposed. The newly added “ability to improve” is related to supply chain redesign in the post-disruption phase. As the survey results show, manufacturing companies take improvement actions to avoid similar disruptions in the future. For example, the researched enterprises “redesign a disrupted process’s structure” the most often. The several hypotheses were confirmed. Additionally, the TBLR construct for the measuring the impact of the disruptions was confirmed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 122-139
Keywords: supply chain resilience; redesign; reconfiguration; discruption; odporność łańcucha dostaw; projektowanie; rekonfiguracja; zakłócenie